(untitled) (Nigerian Journal of Physiological Sciences, 2023)
In spite of the increasing use and importance of the African giant rat (Cricetomys gambianus Waterhouse) in research, and other fields, like location of landmines, there is still not enough information on their physiology. In this study, we assessed the electrocardiogram, blood pressure, vital parameters and anaesthetic indices of the African giant rat (Cricetomys gambianus Waterhouse), both genders, using diazepam or ketamine as chemical restraints. A total of 24 adult African Giant Rats (AGR), 12 males and 12 females were used in this experiment. The animals were divided into two groups of twelve animals each (6 males and 6 females). One group was assessed for the effect of diazepam, and the other group ketamine. Diazepam (Roche®, Switzerland) was administered intraperitoneally at a dose rate of 7.5 mg/kg, while ketamine was administered intraperitoneally at a dose rate of 45 mg/kg. Parameters measured were recorded from the time desirable sedation was achieved, and every 15 minutes till the animal was awake. Animals administered diazepam took a longer time to sleep or achieve desirable sedative state, a longer time to respond to stimuli before waking up fully and a longer time to be fully awake, relative to ketamine-induced sedation. Ketamine caused a continuous increase in respiratory rate and blood pressure, while diazepam caused a continuous decrease in the respiratory rate. The electrocardiogram showed tachycardia throughout the experiment with the use of both drugs, although this was more pronounced with the use of diazepam, causing a decrease in QRS interval and a decrease in QT interval. Gender differences were observed in most parameters measured. The results obtained gave baseline values for electrocardiogram and blood pressure readings, while also detailing the changes and gender differences observed with sedation. In addition, results indicated ketamine is best used for short procedures and diazepam at a higher dose used for procedures requiring longer time in the African giant rat